Effect of elastomer polymer on the moisture susceptibility of asphalt concrete - Shabani Amir; Hamedi Gholam Hossein (Magazine of Civil Engineering, 2022)
There are various experimental methods for improving the moisture strength of asphalt concrete, such that the most common one being the use of anti-stripping materials. In the present paper, the influences of polymer materials on\ asphalt binder were investigated using repetitive loading test in wet and dry conditions along with thermodynamic parameters based on the surface free energy (SFE) components of asphalt binder and aggregates. The obtained results of this investigation indicate that using styrene butadiene rubber (SBR) polymer has improved the asphalt concrete strength against the moisture damage, especially in the specimens made of granite aggregates. Also, SBR polymer increases the cohesion free energy and reduces the energy released by the system during the stripping event, which represents a decrease in the tendency for stripping. The stripping percentage index, which is obtained by combining the results of the repetitive loading test in wet and dry conditions along with the results of thermodynamic parameters, represents that the specimens made of controlled asphalt binder in the loading cycles under wet conditions have a higher stripping rate. Also, the modulus loss rate in control asphalt concrete is faster than the modified specimens.